Energy storage for active network management on electricity distribution networks with wind power. Issue 3 (1st April 2014) - Carr, Stephen; Premier, Giuliano C.; Guwy, Alan J.; Dinsdale, Richard M.; Maddy, Jon
Abstract : Increasing amounts of variable renewable generation are likely to enter the UK's energy systems in the near future. To accommodate this generation onto electricity networks, the concept of active network management (ANM) has become a significant area of research interest. Network connected energy storage systems (ESS) are considered here as a means to actively control the network in order to increase the amount of generation that is possible to connect to a network. ESS is one of several potential methods of ANM, but has not been widely researched in this context. In this study, the ability of the ESS to increase the amount of wind energy accepted onto a network is assessed over a range of roundtrip storage efficiencies. An analysis is then conducted to determine the cost of energy produced through the ESS for a number of scenarios. The results show that the ESS is able to increase the energy accepted onto a distribution network, with the efficiency of the ESS, energy storage capacity, windfarm size, network losses and network characteristics being important in determining the relative effectiveness of the ESS and the cost at which electricity is produced.